Intervensi Goal Setting Dalam Cabang Olahraga Terukur: Systematic Literature Review - Tuliss Bial (Institut Teknologi Bandung, 2022)
Setting goal setting is a motivation that can help someone understand their goals and develop the skills they want to achieve them. This study aims to conduct a comprehensive evaluation of the literature on goal setting interventions in measurable sports. This study uses a systematic method of literature review by searching for the topic of Goal Setting Intervention on Measurable Sports Athletes using international databases, namely Google Scholar, Scopus, Elsevier, Researchgate and the national database, namely SINTA. This study uses keywords in two languages which include: Intervention (intervention), goal setting, athlete (athlete), athletic, rowing, swimming, weightlifting. The criteria are the year of publication in the period 2000-2022 and the research participants are athletes in measurable sports such as swimming, rowing, athletics, rollerblading, weightlifting. The third criterion is that researchers do not include articles whose sports are not included in measurable sports. Selection of articles for review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, which include: (1) defining topics and criteria, (2) determining sources of information, (3) selecting relevant literature, (4) collecting articles and (5) analyzing articles (PRISMA, 2015). Results from this study 385 outcomes were identified, of which 9 were eligible and the eligibility criteria were fully reviewed. It can be concluded from this systematic review that goal setting in measurable sports athletes has a positive influence on athlete performance both in completing training programs, dealing with fear of failure, reducing anxiety, and also in a competition.